2020
DOI: 10.3390/nu12113273
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of (E)-β-Caryophyllene (BCP) in Chronic Inflammation

Abstract: (E)-β-caryophyllene (BCP) is a bicyclic sesquiterpene widely distributed in the plant kingdom, where it contributes a unique aroma to essential oils and has a pivotal role in the survival and evolution of higher plants. Recent studies provided evidence for protective roles of BCP in animal cells, highlighting its possible use as a novel therapeutic tool. Experimental results show the ability of BCP to reduce pro-inflammatory mediators such as tumor necrosis factor-alfa (TNF-α), interleukin-1β (IL-1β), interleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 178 publications
(277 reference statements)
1
54
0
1
Order By: Relevance
“…Until now, physical activity of students during this pandemic in relation to their well-being has been already investigated in some studies: During the pandemic the amount and type of physical activity and sport decreased—with only 30% of university students achieving a “sufficient” level of activity (Gallo, Gallo, Young, Moritz, & Akison, 2020 ). In a study with students from the United States it was shown that the total minutes of physical activity were related to positive affect before and during the stay-at-home orders.…”
Section: Physical Activity Sports and Well-being In Students During The Coronavirus Pandemicmentioning
confidence: 99%
“…Until now, physical activity of students during this pandemic in relation to their well-being has been already investigated in some studies: During the pandemic the amount and type of physical activity and sport decreased—with only 30% of university students achieving a “sufficient” level of activity (Gallo, Gallo, Young, Moritz, & Akison, 2020 ). In a study with students from the United States it was shown that the total minutes of physical activity were related to positive affect before and during the stay-at-home orders.…”
Section: Physical Activity Sports and Well-being In Students During The Coronavirus Pandemicmentioning
confidence: 99%
“…Some studies have demonstrated it has different biological properties, such as antifungal [ 42 , 43 ], antileishmanial [ 44 ], and antitrypanosomal properties [ 45 , 46 ]. Lately, studies have been focusing on other qualities, such as its anti-inflammatory [ 47 ], antidiabetic [ 48 ], and anticancer and chemopreventive properties [ 41 , 43 ]. Nevertheless, fewer studies refer to the antibacterial properties of β -caryophyllene.…”
Section: Resultsmentioning
confidence: 99%
“…It contributes to the unique aromas of essential oils and plays a pivotal role in the evolution and survival of higher plants. Furthermore, studies have provided evidence that support β-caryophyllene as a potential therapeutic tool based on the protective roles it exhibits on animal cells [ 316 ]. Moreover, experimental results have noted the ability of this molecule to reduce effects of chronic pathologies characterized by inflammation and oxidative stress, especially metabolic and neurological diseases [ 316 ].…”
Section: Chemical Compoundsmentioning
confidence: 99%
“…Furthermore, studies have provided evidence that support β-caryophyllene as a potential therapeutic tool based on the protective roles it exhibits on animal cells [ 316 ]. Moreover, experimental results have noted the ability of this molecule to reduce effects of chronic pathologies characterized by inflammation and oxidative stress, especially metabolic and neurological diseases [ 316 ]. β-Caryophyllene has exhibited beneficial effects on diabetes, cardiovascular diseases, obesity, some liver diseases, pain and other nervous system disorders [ 316 ].…”
Section: Chemical Compoundsmentioning
confidence: 99%